The mediating role of customer satisfaction on the effect of service quality on post-purchase intention - Aziz, Agus Abdul (Universitas Ahmad Dahlan, 2024)
Purpose-This study aims to analyze the relationship between service quality and post-purchase intention, with customer satisfaction as a mediating variable, specifically targeting provider Telkomsel users in Indonesia. Design/Methodology/Approach-Data were collected from user provider Telkomsel in Indonesia and the number of respondents obtained was 96. This study used Smart PLS for data analysis, examining correlations between variables, and assessing moderation effects. Findings-This study's findings indicate a positive relationship between service quality and post-purchase intention among provider Telkomsel users in Indonesia. In addition, customer satisfaction is proven to mediate this relationship. Research limitations/implications-This study still has limitations despite its contributions. The results are based on data collected from Telkomsel provider users in Indonesia, so they cannot be used to describe the consumer behavior of providers other than Telkomsel in Indonesia. Future research can increase the sample size and choose other providers to increase the variation in the results of this study. Originality/value- This study contributes to previous research by filling the gap and providing new insights into the factors that influence post-purchase intention, especially in the context of Telkomsel provider users in Indonesia. This study considers service quality and customer satisfaction as mediators by uncovering the mechanisms underlying post-purchase intention.